From the clinic to the classroom: a pathway for physician assistants/associates into academia - Jonathan T. Baird; Lauren Stanford; Tyler Sommer (Springer, 2024)
Abstract This brief communication proposes a possible model for training clinically practicing Physician Assistants/Associates (PA) for a transition into academic medicine. Demand for full-time PA educators is rising. Most new full-time PA educators come from clinical practice and find the transition challenging, resulting in attrition. There is no uniform, expected pathway for PAs wanting to transition into academia, however several institutions have developed fellowships in recent years. Traditionally, residencies have given medical providers, mainly physicians, training for specialty areas of medicine, though only some of those have been wholly devoted to full-time academic medicine. The reasons for their absence are beyond the scope of this paper. It is not uncommon for universities and educational hospitals to experience budget constraints when considering establishing a residency training program. The authors describe the part-time residency at their institution for PAs desiring to be educators, succinctly describe their process and outcomes, and propose it as a model for emulation.